Sustainable production of wind energy in the main Morocco's sites using permanent magnet synchronous generators. (9th March 2020) - El Mourabit, Youness; Derouich, Aziz; Allouhi, Amine; El Ghzizal, Abdelaziz; El Ouanjli, Najib; Zamzoumyes, Othmane
Summary: This paper assesses the behavior of a wind energy conversion system (WECS) under the fuzzy control in several sites located in Morocco. The sites involved in this study are located in coastal areas, namely, Assila, Houceima, Tetouan, Dakhla, Essaouira, and Laayoun. Furthermore, the first part deals with an inventory and state of art of the wind potential, achievements, work in progress, and future projects in the Kingdom of Morocco. Subsequently, a statistical analysis of the wind data and concerning the wind speed and direction in relevant geographical areas was presented in detail. The second part of the paper examines the control of WECS which is based on the direct control of the permanent magnet synchronous generator. Generator connection to the power grid is achieved by two power converters in back‐to‐back configuration controlled by pulse width modulation. The whole system modeling including the generator modeling was discussed. The control development based on (Fuzzy‐proportional‐integral) corrector for the machine‐side converter and the maximization of the power extracted from the wind using the maximum power point tracking technique have been developed. The grid‐side converter ensures the system connection to the grid with good power quality and controls the DC bus voltage. The control strategy is verified through the simulation in the Matlab‐Simulink environment to validate and evaluate the dynamic performance of the system using real wind measurements for the selected sites. The obtained results prove the effectiveness of the intended control. Interestingly, the southern zone of Morocco is more convenient for the exploitation of electricity production compared to the northern zone of the country which it can be beneficial for autonomous applications.